TINJAUAN MENGENAI TINDAK PIDANA PELECEHAN SEKSUAL DALAM SISTEM PERADILAN PIDANA DI INDONESIA DIKAJI DARI PERSPEKTIF GENDER - M. Arief Deka Rizqi; Erdianto Erdianto; Davit Rahmadhan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
As a follow-up to the incomplete regulations, the government passed Law No. 12 of 2022concerning Crimes of Sexual Violence which in the Act does not limit the perpetrators or victims.This means that harassment by men against women and vice versa or by men against men and viceversa is still considered an act of sexual violence . Even so, we cannot close our eyes that sexualharassment and violence against men does exist and needs to be eradicated just like sexualviolence against women .The purpose in writing this thesis, namely: First , To Know Formulation of the Crime ofSexual Harassment in the Criminal Justice System Reviewed From a Gender Perspective . Second,To know Criminal Law Policy Against Countermeasures Gender Based Sexual Harassment .Type research used in study This is study law normative . In study normative This writer dostudy to principles of law .From the results of the study it was found that the formulation of the crime of sexualharassment in the criminal justice system in Indonesia, especially against men, is in Article 5 andArticle 6 of the TPKS Law where the main punishment can be in the form of imprisonment andspecial rehabilitation, and additional punishment can be in the form of compensation, deprivationprofits derived from criminal acts, social work, special coaching, revocation of parental rights,revocation of political rights, and revocation of the profession. This form of punishment provides ahigher burden of deterrent effect. Not only sentenced to prison, but also other additional crimesthat are also more burdensome. Legal Policy criminal action against gender-based sexualharassment efforts is through the means at outside of criminal law ( non-penal policy ), namely inthe form of preventive measures such as provide an understanding of gender-based harassment byorganizing special classes, such as Weekend Class . This should be a crime prevention effort whoare at the forefront, because as the saying goes that prevention is better than cure.Author's suggestion, First, the Law on Sexual Violence Crimes must be implemented moreoptimally so that the use of articles in cases of sexual violence becomes more targeted.Second, protection for victims of sexually harassing behavior must be maximized and become thefocus government's role in law enforcement .Keywords: Sexual-Gender-Criminal Harassment